Comparison of the Efficiency of Two Taping Techniques in Reducing Thoracic Kyphosis among Girls Aged 18-30 Years - Farzaneh Moslemi Haghighi; Katayoon Rezaei; Zahra Etminan; Habibollah Lari (Shiraz University of Medical Sciences, 2019)
Background: Kyphosis means an abnormal increase in the curvature of the thoracic region of the vertebral column and refers to a situation where the thoracic kyphosis range is more than forty five degrees. Vertebral column taping seems to be one of the most effective ways of treating kyphosis. The aim of this study was to investigate and compare the effect of two taping techniques in reducing the degree of kyphosis in girls aged 18-30 years. Methods: Thirty-two volunteers were randomly assigned into two groups (n=19 per group) of V-shaped tape and I-shaped tape. Taping techniques were performed as follows by applying 50% tensile force: V-shaped tape: The tape started on both sides of the anterior of acromioclavicular joint and extended to the spinous process of T6 vertebra. I-shaped tape: The patient's body was kept in a standing and straight state and then a longitudinal tape was applied from T1 to the deepest lumbar lordosis region. The measurements were carried out before, immediately, 24, and 48 hours after taping by a flexible ruler in a similar manner. Data analysis was performed using Friedman Test, Kolmogorov-Smirnov Test, Wilcoxon Signed Rank Test and Mann Whitney Test. Results: The results of this study showed a significant reduction in the degree of kyphosis in the case of the V-shaped tape 48 hours after taping. However, the degree of kyphosis decreased after 24 h (P=0.001) and 48 hours (P< 0001) in the I-shaped tape group. In addition, there was no significant difference between the two interventions in terms of decreasing the degree of kyphosis at any time interval except for 24 hours (P=0.043). Conclusion: Taping reduces the degree of kyphosis by creating mechanical support, creating proprioceptive feedback, affecting the proprioception, improving the function of spinal erectors, and improving the mental image of the body with kyphosis. It appears that the I-shaped tape positioning on the alignment of spinal erectors spine makes it more effective.